EFIKASI DIRI MENINGKATKAN KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK YANG MENJALANI TERAPI HEMODIALISIS - Safruddin, Safruddin; Ulfah Mutthalib, Nurul (Bina Generasi : Jurnal Kesehatan, 2024)
Hemodialysis therapy is routinely conducted on end-stage chronic kidney disease patients approximately 2-3 times a week for the patient's survival. However, numerous physical, psychological, and socio-economic problems arise in patients due to routine hemodialysis, thereby impacting the patient's quality of life. This study aims to determine the relationship between self-efficacy and the quality of life of end-stage renal disease (ESRD) patients undergoing hemodialysis (HD). The research employs an analytical observational design with a cross-sectional study approach. The study population includes all end-stage renal disease patients, and the sampling technique is accidental sampling, with a sample size of 80 patients. Data analysis involves univariate and bivariate analyses to examine the relationships among variables using statistical tests, specifically the Spearman correlation test. There is a positive correlation between self-efficacy and quality of life in the physical domain with a p-value 0.001, in the psychological domain with a p-value 0.001, in the social domain with a p-value 0.001, and in the environmental domain with a p-value 0.001.Self-efficacy has a significantly positive correlation with the improvement of the quality of life in the physical, psychological, social, and environmental domains among hemodialysis patients, with a p-value < 0.005